Cilia and centrosomes: Ultrastructural and mechanical perspectives. (February 2021) - Ishikawa, Takuji; Ueno, Hironori; Omori, Toshihiro; Kikuchi, Kenji
Abstract: Cilia and centrosomes of eukaryotic cells play important roles in cell movement, fluid transport, extracellular sensing, and chromosome division. The physiological functions of cilia and centrosomes are generated by their dynamics, motions, and forces controlled by the physical, chemical, and biological environments. How an individual cilium achieves its beat pattern and induces fluid flow is governed by its ultrastructure as well as the coordination of associated molecular motors. Thus, a bottom-up understanding of the physiological functions of cilia and centrosomes from the molecular to tissue levels is required. Correlations between the structure and motion can be understood in terms of mechanics. This review first focuses on cilia and centrosomes at the molecular level, introducing their ultrastructure. We then shift to the organelle level and introduce the kinematics and mechanics of cilia and centrosomes. Next, at the tissue level, we introduce nodal ciliary dynamics and nodal flow, which play crucial roles in the organogenetic process of left–right asymmetry. We also introduce respiratory ciliary dynamics and mucous flow, which are critical for protecting the epithelium from drying and exposure to harmful particles and viruses, i.e., respiratory clearance function. Finally, we discuss the future research directions in this field.